Relationship between contrast-induced nephropathy and long-term mortality after percutaneous coronary intervention in patients with chronic coronary total occlusion - Güzel,Tuncay (2022)
SUMMARY OBJECTIVE: Intervention in chronic total occlusion lesions involves long procedure time, a serious contrast load, and complex procedures. In this study, we aimed to investigate mortality rate of patients who had procedural coronary angiography done for chronic total occlusion lesions in coronary angiography series and who developed contrast-induced nephropathy. METHODS: A total of 218 patients with chronic total occlusion lesion in at least one coronary artery, from three different medical centers, who underwent procedural coronary angiography were recruited for the study. Patient population was divided into two groups: those who developed contrast-induced nephropathy and those who did not. Mortality due to all causes was investigated between both groups throughout a 100-month follow-up. RESULTS: Mean age of patients with incidence of contrast-induced nephropathy was 66.7±11.8, and 23.8% of them were comprised by female. We found a significantly higher mortality in long-term follow-up in the patient group with contrast-induced nephropathy (42.9 vs. 57.1%, p≤0.001). According to Kaplan-Meier analysis performed additionally, survival during follow-up was significantly shorter in this group and, in logistic regression analysis, it was an independent predictor of mortality (OR 3.02; 95%CI 1.41–6.45, p=0.004). CONCLUSION: We identified that the development of contrast-induced nephropathy is associated with long-term mortality. It might be possible to reduce adverse events with prophylactic approaches before the procedure and close follow-up of such patients after the procedure.